Effective pedagogical means of preventing posture disorders - Egorov A.S. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the optimal means of preventing posture disorders in students. Methods and structure of the research. Anthropometric measurements, posture measurements, as well as a survey of 110 first-year students of the National Research TSU of the main medical group were carried out. Research results and conclusions. According to the measurement results, reversible postural disorders of the initial stage were identified in 60% of students and deviations from normal body weight in 80%. The article discusses various technologies for the prevention of postural disorders, and also identifies the optimal means of preventing postural disorders in students in the process of physical education. A new pedagogical technology for the prevention of postural disorders in students is proposed. Introduction. In the last decade, there has been a negative trend in the health of student youth. According to scientific research, up to 80% of first-year students have various functional deviations or various chronic pathologies. One of the most common deviations is posture disorders. Due to the high rate of development of information technologies, actively used in the learning process both in higher education institutions and schools, it leads to a decrease in physical activity. The use of various gadgets is dictated by both educational activities and dependence on social networks and computer games. All this is accompanied by a sedentary lifestyle and are negative factors leading to posture disorders [6, 7].